SEED LONGEVITY UNDER THE CONTROLLED CONDITIONS - Задорожна, О. А.; Герасимов, М. В.; Шиянова, Т. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The determination of the optimal conditions for storage as active seed collections as longterm seed storage collections needs analysis of the monitoring results of seed germination of 38 buckwheat (Fagopyrum esculentum Moench.) and tatar buckwheat (Fagopyrum tataricum (L.) Gaertn.) accessions of different gene pool categories. These accessions were received from different Institutions of Ukraine and the Russian Federation and storaged under controled conditions. Before the lying to storage seeds were dried at a temperature no higher than 25oC it was recommended moisture content 5-8 %. Seeds were storage in airtight containers in the depository under uncontrolled conditions of temperature and in the depositories at low temperatures 4oC or at the negative temperature minus 18-20oC. Study of seed germination conducted in accordance with the International Rules for Seed Testing. It is shown that the possibility of conservation of the initial buckwheat seed germination level to ten years or more provided under maintaining seed moisture 5-8%, which is achieved by drying in special conditions at temperatures no higher than 25oC. It’s allowed seeds’ storage in airtight containers under uncontrolled temperature conditions, at 4oC or -20oC. During long term buckwheat seed storage were sometimes observed germination fluctuations that can be explained by a change in the content of phytohormones during storage.